Portefeuljebestuur, die kapitaalmarkprysmodel en verwante tegnieke - J. Van Zyl Smit (South African Journal of Business Management, 1990)
– The importance of risk management in business has long been recognised. The importance, assumptions and limitations of the Capital Asset Pricing Model is generally accepted and an elaborate introduction is therefore not necessary. The stability of returns on investments is both a measure of risk and a cardinal determinant of the Capital Asset Pricing Model which deals with risk and reasonable return. The Capital Asset Pricing Model as prospective valuation instrument is subject to serious limitations. Certain determinants of the model can however be shown to be of great theoretical and practical importance in techniques of prospective value. To develop a theoretically sound practical return measure with predictive value to be applied in conjunction with the Capital Asset Pricing Model would constitute a meaningful contribution to investment management. This article is based on a study carried out on a small sample of companies quoted on the Johannesburg Stock Exchange during the period 1982 to 1990 with a view to illustrate the application in portfolio management of the Capital Asset Pricing Model and its short-term predictive value in respect of share price movements. In addition a number of techniques complementary to the Capital Asset Pricing Model were developed and illustrated.
Keywords: 650